QUALITATIVE EVALUATION: EFFECTIVENESS FOR THE USE OF DIGITAL / SOCIAL MEDIA EDUCATION (Contemporary Journal of Social Science Review, 2025)
The purpose of the study is to confirm the applicability of digital media and social networks in learning and acknowledge the potential of using networks in the construction of knowledge. It is used survey approach by asking the attitude. Concerning the social media usage in education among teachers and students in Karachi. It is concluded that the technological approach enables the teacher and learner to understand each other better during the teaching learning process, hence making communication the current life of all groups through a more sensitive teaching process.